(3JhVjM GdecGSHs - (3GdfLaj, GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdNQGL hGdebGSeI, bhdg eG jCNPg GdSdWGf SjLjA Cfg aj GdJfHjg GdQGHY ef JfHjgGJ GdeSFdI GdeQGO ef GdSdWGf bhdg GdeSJMd dCNP GdNQGL GMJQR ef ZjQ GdeSJMds
(3BNQgG (B:s
(3BNQgG(B: (3heG jbGd ef Cf GdedReGJ dG JhLH GdedcjI aajg Cf GdedcjI EPG de JMUd dG jchf gfGc GdRGe dCf GdEHGMI djSJ EdG Mce TQYj ddeGdcs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis